Pendampingan Teknis Pembangunan Gereja Jemaat Hatunuru- Matapa di Kecamatan Taniwel Kabupaten Seram Bagian Barat - Ohorella, Fuad Hasan (Universitas Borneo Tarakan, 2024)
The building is one of human needs and is used as a place to live and various other activities. The function of the building includes residential and religious. Administratively, Hatunuru-Matapa Village is in East Taniwel District. The Immanuel Church building is a public facility to serve the congregation from Hatunuru-Matapa Village, so the renovation of the Church was carried out independently to improve service. Lack of understanding of building work and the use of good materials can cause errors in Immanuel Church renovation work. Technical assistance for the community, which aims to increase the knowledge and skills of the community in carrying out building work according to their needs and taking into account aspects of the strength of building construction according to applicable regulations. The results of this dedication show that the participants experienced an increase in knowledge and skills about building construction work and the selection of materials.